Invigorate Survival and Resilience of MSMEs: The Role of Entrepreneurial Knowledge, Entrepreneurial Motivation, and Technological Advancement - Bagis, Fatmah; Faridli, Efi Miftah; Suyoto, Suyoto; Awaludin, Agus; Umairoh, Jovinda Percillia Ma’rifatul (Research Synergy Foundation, 2024)
Entrepreneurship is currently experiencing significant and dynamic development. The growth rate of entrepreneurship is a sensitive issue and challenge that attracts public attention in the middle of increasingly tight competition. The development of entrepreneurship is driven by various factors, including rapid technological development and globalization. However, with the development of technology, entrepreneurship also needs to have good preparation to face increasingly tight levels of competition and can maintain and create increasingly successful entrepreneurship. Therefore, this study aims to determine the factors that influence the sustainability resilience and survival of MSMEs. A quantitative method was used in this study, and incidental sampling was used to select 238 MSMEs as respondents. The distribution of questionnaires was carried out openly to MSMEs through associations that oversee the performance of MSMEs. Data analysis in this study used the Structural Equation Model (SEM) and Partial Least Squares (PLS) analysis software version 3.0. The results of the study indicate that entrepreneurial knowledge has a positive effect on the sustainability resilience and survival of entrepreneurs, entrepreneurial motivation has a positive and insignificant effect, and technological progress has a positive and insignificant effect. This study provides new contributions and knowledge that an entrepreneur must be able to know what preparations must be made and how they can manage MSMEs in the midst of competition to anticipate conflicts that will occur in the future.